Making Multicultural Families in Europe Gender and Intergenerational Relations (Cham : Springer International Publishing, 2018)
This edited collection explores family relations in two types of 'migrant families' in Europe: mixed families and transnational families. Based on in-depth qualitative fieldwork and large surveys, the contributors analyse gender and intergenerational relations from a variety of standpoints and migratory flows. In their examination of family life in a migratory context, the authors develop theoretical approaches from the social sciences that go beyond migration studies, such as intersectionality, the solidarity paradigm, care circulation, reflexive modernization and gender convergence theory. Making Multicultural Families in Europe will be of interest to students and scholars across a range of disciplines including migration and transnationalism studies, family studies, intergenerational studies, gender studies, cultural studies, development studies, globalization studies, ethnic studies, gerontology studies, social network analysis and social work.‰.
1. Editors' introduction: Aims, scope and structure of the book; Laura Merla, Stefania Giada Meda, Isabella Crespi -- 2. Introducing transnational and mixed families; Stefania Giada Meda & Isabella Crespi -- Part I: Multi-ethnic families: Negotiating Difference across Gender and Generations -- 3. Global householding' in mixed families: the case of Thai migrant women in Belgium; Asuncion Fresnoza-Flot & Laura Merla -- 4. 'Doing gender' across cultures: Gender negotiations in bi-national couple relationships; Benedicte Brahic -- 5. Reversal of the Gender Order? Male Marriage Migration to Germany by Turkish Men: new forms of gendered transnationalization of migrant offsprings in Europe; Ursula Apitzsch -- 6. Comparing sibling ties in inter-ethnic and intra-ethnic families in Germany; Ebru Balaban, Dafina Kurti & Jara Kampmann -- 7. Intercultural Negotiations over a Newborn: the case of Persians in the United Kingdom; Ali Amirmoayed -- Part II: Transnational families: managing care and intimate relationships at a distance -- 8. Gender and Care in Transnational Families: Empowerment, Change and Tradition; Lise Widding Isaksen -- 9. Intimacies of power in the circulation of care: making gender across generations. Transnational Andean families in Quito and Madrid; Gregory Dallemagne -- 10. "And They Shall Be One Flesh...?": Gender convergence of family roles in transnational families of Ukrainian migrant women; Alissa V. Tolstokorova -- 11. Intergenerational Solidarity in Romanian Transnational Families; Mihaela Hărăguș & Viorela Telegdi-Csetri -- 12. Transnational families in Lithuania: multi-dimensionality and reorganization of relationships; Irena Juozeliūnienė, Irma Budginaitė & Indrė Bielevičiūtė -- 13. Not fit for migration with teenage children - Polish transnational immigrant families in Ireland; Beata Sokolowska -- 14. Distant relationships in transnational families and kinship networks: The case of Turkish migrants in Germany; Eveline Reisenauer -- 15. Migration Matters: Insights into intergenerational Solidarity Patterns in Europe; Ronny König, Bettina Isengard, & Marc Szydlik.
Social Sciences
text file PDF
Keywords: Social groups; Family; Culture; Sociology